Nutrient transport characteristics of livestock manure in a farmland - Yunhee Lee; Seong-Wook Oa (International Journal of Recycling of Organic Waste in Agriculture)
Background: Livestock excretions containing high concentration of nutrient, pig liquid fertilizer, and cattle manure were applied to agricultural land. The characteristics of nutrient transport were examined in surface runoff and groundwater by an artificial rainfall event at real scale field site. Also, the effects of the artificial rainfall event on the characteristics of residual soil after the rainfall and phosphorus adsorption capacity were evaluated in the lab. Results: As results from the field experiments, nitrogen concentration was decreased by the repeatable precipitation in surface runoff, but the nitrate concentration in groundwater was gradually increased by biological metabolism, especially with pig liquid fertilizer. Phosphorus was mostly adsorbed into the soil, and its reduction was affected by the soil drainage due to surface runoff in summer. The adsorption capacity of the phosphorus via a jar test was determined as 0.7 mg P/kg of soil. Conclusion: The soil adsorption capacity would be an important factor for the optimum level of nutrient application that is required for agricultural performance and minimal environmental impact.